Comparative Analysis of expression patterns among the ribosomal protein genes of rpl27, rpl37a, and rpl41 in human cell line - Chin, Fiona Sze Yen (Universiti Malaysia Sarawak, UNIMAS, 2013)
Ribosomal proteins are essential in protein biosynthesis process and they also have extraribosomal functions. These proteins have been found to be closely associated with various inherited diseases and cancers. Previous studies revealed that the ribosomal protein large subunit (RPL) gene expressed differently among cell line derived from human nasopharyngeal carcinoma (NPC). However, RPL27, RPL37a, and RPL41 are found to be significantly downregulated in all cell lines derived from NPC tumours when compared to normal control. The main objective of this study is to evaluate quantitatively the expressed transcript level among the RP genes of RPL27, RPL37a, and RPL41 in the human cell line system. The method of Reverse Transcription Polymerase Chain Reaction (RT-PCR) coupled with band intensity analysis will be used to meet this objective. Result from this finding show that there are no significant different in expressions of RPL27, RPL37a, and RPL41 in NPC tumours and normal control. Besides that, RPL27 and RPL37a show significant correlation when increase in sample size.